Diseño, construcción, instalación y puesta en marcha de una planta piloto de tratamiento de aguas residuales provenientes del camal municipal del cantón Machala. - Reyes Quevedo, Priscila E (2013)
The system design of treatment of residual originating waters of the municipal halter, it correspond to the suggested for the American Health Organization, which advises not to pour the waste matter generated by the killing of animals of coral in the sewage systems to to cause radio receivers like rivers.